An Assessment of the principles of control over notarial activities in Ukraine - Servetnyk, Anna; Popovich, Iryna; Antol, Iryna; Krasnohor, Oleksandr; Bolgar, Oleg; Kolotilova, Tetiana (DIXI, 2025)
Understanding the principles of control over notarial activities is impossible without first examining their historical origins. These principles have long been a cornerstone of Ukraine’s national legal tradition. Although the specific principles of notarial oversight were not explicitly outlined in the Ruska Pravda, it was during that period that the ideological, cultural, and ethical foundations for the development of national public service were established. It is essential to recognize that moral and ethical principles must remain a fundamental component of the notary profession, as they play a crucial role in overseeing notarial activities in Ukraine. Ethical leadership, which is of paramount importance in both higher education and civil service, should be rooted in strong moral character and responsible management. The principle of digital transparency in the oversight of notarial activities has emerged as a means of enhancing public administration efficiency, reducing administrative costs, improving the quality and accessibility of public services, and combating corruption. Additionally, ensuring the high professionalism of notaries involves developing specialized skills, such as working with veterans and military personnel, engaging in public activism, and fostering legal education through interaction with the public as part of the Notary Chamber of Ukraine’s initiatives. Finally, the principle of judicial oversight over notarial activities, with a focus on protecting human rights and freedoms, naturally stems from the provisions of the Constitution of Ukraine and the European Code of Notarial Ethics. This oversight serves as a safeguard for the rights and freedoms of citizens.